ANALISA DETERMINAN YANG BERHUBUNGAN DENGAN PENYAKIT TUBERKULOSIS (TBC) DI RSUD PROF. DR. MARGONO SOEKARJO - Sunani, Aan; ., Ratifah (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2014)
Tuberculosis is one of the infectious diseases caused by the bacteria named mycobacterium tuberculosis and usually experienced by poor people with low economic levels. Tuberculosis can be caused by several factors such as a hospital chart of tuberculosis in the family, parental smoking behavior and the condition of the home environment. To know the determinants associated with tuberculosis in toddlers in Prof. Dr. Margono Soekarjo hospital Purwokerto. This study is an observational study with case control design. The population is toddlers’ parents who are affected by Tuberculosis. Toddlers’ parents who are not affected by tuberculosis amounted to 116 people and each sample was taken as many as 54 people. The data analysis method uses Chi Square test. There is a correlation between a hospital chart of tuberculosis in the family with tuberculosis in infants (p value = 0.000). There is a correlation between smoking behavior in families with infants Tuberculosis incidence (p value = 0.001). There is a correlation between the condition of the home environment with the incidence of tuberculosis in infants (p value = 0.001). There is a correlation between a hospital chart of tuberculosis in the family, parental smoking behavior and the condition of the home environment with tuberculosis in infants in Prof. Dr. Margono Soekarjo hospital Purwokerto. Keyword: Tuberculosis disease in the family history, family smoking behavior, home environment toddlers, Tuberculosis in toddlers